Correlation between levels of patient satisfaction and the value of cephalometric skeletal analysis in post-orthognatic surgery patients - Joni Putra; Endang Sjamsudin; Asri Arumsari; Abel T. Yuza (Journal of Dentomaxillofacial Science, 2022)
Objective: The purpose of this study was to analyze the level of patient satisfaction after orthognathic surgery and the correlation between the patient satisfaction level after orthognathic surgery and the results of the cephalometric skeletal analysis. Material and Methods: This study were patients who had orthognathic surgery either BSSO, Osteotomy Le Fort 1, or Double Jaw Surgery. First, the subjects filled out a questionnaire about patient satisfaction after orthognathic surgery, the second was taking cephalometric radiographs which were then analyzed by the Steiner method by measuring the angles of SNA, SNB, ANB, and GoGN-SN. Results: The results of the study on 10 research subjects showed that all questionnaire scores were in the "satisfied" category. Cephalometric skeletal analysis of all cephalograms showed 50% normal SNA angle, 10% normal SNB angle, 80% normal ANB angle, and 90% normal GoGN-SN angle. The Concordal Kendall test results show the correlation coefficient value of 0.534 or 53.4%. Conclusion: On average, patients are very satisfied with the orthognathic surgery they have undergone. There is a correlation between the level of patient satisfaction after orthognathic surgery and the results of the cephalometric skeletal analysis.